Administration of estates in Malaysia: Law and procedure. By Akmal Hidayah Halim. Selangor, Malaysia: Sweet Maxwell & Asia, 2012, pp. 221. ISBN: 9789675040849 - Wan Muhammad, Ramizah (IIUM Press, 2012)
Akmal Hidayah Halim, the author of the volume under review, has earlier published The Law of Wills and Intestacy in Malaysia (Selangor, Malaysia: International Islamic University Malaysia, 2009). Administration of Estates in Malaysia is based on the author’s Ph.D. thesis. The subject matter of this book is extremely important in the legal fraternity as it deals with property left by the deceased. There are many cases in Malaysia where the money and property left by the deceased has gone unclaimed either because the members of general public were unaware of the procedure to follow in claiming the estates or because the deceased failed to name the legal administrator of the estate upon his/her death.